2022
DOI: 10.1111/jgs.18032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment preferences among adults with normal cognition and cognitive impairment

Abstract: Background: Although patient participation in treatment decisions is important for preference-concordant care delivery, it is largely unknown how cognitive impairment influences treatment preferences. We investigated whether treatment preferences for the care of serious illness differ between adults with and without cognitive impairment in hypothetical clinical scenarios.Methods: Data from the 2018 Health and Retirement Study were used. The sample included 1291 self-respondents (201 respondents with cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…As such, it is important for PLWD to discuss their healthcare goals and values and future care preferences as their disease progresses 7 . For PLWD, this is best done early in the illness trajectory when they can express what matters most to them, personal definitions of quality of life, and treatment preferences, commonly described as advance care planning (ACP) 8,9 . As dementia progresses and PLWD lose decisional capacity and communication ability, their care partners must take a large role in helping make medical decisions for them 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is important for PLWD to discuss their healthcare goals and values and future care preferences as their disease progresses 7 . For PLWD, this is best done early in the illness trajectory when they can express what matters most to them, personal definitions of quality of life, and treatment preferences, commonly described as advance care planning (ACP) 8,9 . As dementia progresses and PLWD lose decisional capacity and communication ability, their care partners must take a large role in helping make medical decisions for them 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…7 For PLWD, this is best done early in the illness trajectory when they can express what matters most to them, personal definitions of quality of life, and treatment preferences, commonly described as advance care planning (ACP). 8,9 As dementia progresses and PLWD lose decisional capacity and communication ability, their care partners must take a large role in helping make medical decisions for them. 9,10 Research examining ACP interventions have revealed significant variability in the use of standardized versus nonstandardized outcome measures, making evaluation of ACP effectiveness challenging.…”
Section: Introductionmentioning
confidence: 99%